PLEASE HELP ASAP!!


4x - 9y =9

-x + 3y = 6


Rewrite one of the two equations above in the form ax + by = c, where a, b, and c are constants, so that the sum of the new equation and the unchanged equation from the original system results in an equation in one variable.

Respuesta :

It seems like you are solving a system of equations by elimination. One way to solve eliminate a variable would be to multiply the last equation by 3:


4x - 9y = 9 --------------> 4x - 9y = 9


3(-x + 3y = 6) -----------> -3x + 9y = 18

-------------------------

x = 27



The -9y and 9y cancel out if you multiply the bottom equation by 3.